2013
DOI: 10.1021/ie402930x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Parameters Affecting the Visible-Light-Induced Photocatalytic Activity of Monoclinic BiVO4 for Water Oxidation

Abstract: Monoclinic BiVO 4 powders have been synthesized by means of homogeneous coprecipitation, followed by calcination at different temperatures. The effect of the calcination temperature on the changes in the physicochemical parameters has been evaluated. It has been deduced that the crystallite size and band gap are responsible for water oxidation. The effect of calcination temperatures on the variations, such as lone pair distortions on Bi 3+ and changes in the V−O bond length in the local structure of BiVO 4 , h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 27 publications
(43 reference statements)
5
66
1
Order By: Relevance
“…The crystallite size was found to have a direct correlation to the O 2 production activity of BiVO 4 samples [62] (i.e., doubling the size of the BiVO 4 crystals, from 90 to 170 nm increased the rate of O 2 evolution in 5-fold). The preferential orientation towards the {040} facets with respect to the {110} exposed surfaces, is known to have a positive influence on the water oxidation photoactivity of scheelite monoclinic BiVO 4 [63].…”
Section: Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystallite size was found to have a direct correlation to the O 2 production activity of BiVO 4 samples [62] (i.e., doubling the size of the BiVO 4 crystals, from 90 to 170 nm increased the rate of O 2 evolution in 5-fold). The preferential orientation towards the {040} facets with respect to the {110} exposed surfaces, is known to have a positive influence on the water oxidation photoactivity of scheelite monoclinic BiVO 4 [63].…”
Section: Strategiesmentioning
confidence: 99%
“…On the other hand, Thalluri et al [62] identified the important role of the superficial amounts of W and Mo dopants for the water oxidation reaction. They determined that charge carriers separation is enhanced on the surface of BiVO 4 for up to a certain amount of such dopants: 0.9 at.% of W or 1.2 at.% of Mo, for which the superficial electron-hole recombination is reduced, and in turn, the BiVO 4 photocatalytic activity is improved.…”
Section: Addition Of N-type Conductivity Dopantsmentioning
confidence: 99%
“…However, regardless of this, this kind of experiment is usually performed since it is useful to compare the rate of oxygen production (RO 2 ) of the different samples [41][42][43]. The RO 2 of all the samples was calculated through the slope of the cumulative curves in the first 5 minutes of each measurement, and the results are reported in the Table 1 In our previous works, it was observed that the O 2 evolution activity of BiVO 4 had a direct correlation (in order or importance) with the crystallite size, band gap and the ratio between the {040} and {110} facets [13,28]. However, when the O 2 evolution rates of the BiVO 4 , W-BiVO 4 -1 and Mo-BiVO 4 -2 samples (which have similar particles sizes) are compared, it is evident that the crystallites size cannot be correlated to the enhanced activity in the doped materials.…”
Section: Water Oxidation Photo-catalytic Performance Of Doped Bivo 4 mentioning
confidence: 99%
“…Monoclinic BiVO 4 has attracted considerable attention, owing to its water splitting [13] and organic dye degradation [14] photoactivities under visible light illumination. In 1998, Kudo's group first reported monoclinic BiVO 4 that showed promising water oxidation activity under visible light illumination [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation